Opportunities and Challenges for Using Artificial Intelligence Technology in Human Resource Management - Budi Rismayadi (Journal Of Data Science, 2024)
This research aims to identify the challenges and opportunities that arise along with the use of Artificial Intelligence (AI) Technology in the context of human resource management (HR). In the era of digital transformation, organizations are increasingly integrating AI to increase the efficiency and effectiveness of HR management. This research uses a qualitative approach with descriptive methods. The research results show that the use of Artificial Intelligence (AI) Technology in Human Resources Management (HRM) has a significant impact on the efficiency and effectiveness of workforce management. Implementing AI in recruitment processes, performance management and employee skill development can increase productivity and provide in-depth data analysis. However, the research also identified several challenges, including the impact on lower-end jobs, increased equipment maintenance costs, and the need for highly qualified professionals. Therefore, the research conclusions highlight the need for a holistic approach in addressing these challenges, involving employee engagement, investment in training, and collaboration with educational institutions to achieve sustainable and competitive human resource management in the era of AI technology.